STUDY OF PREVALENCE OF POLYCYSTIC OVARIAN SYNDROME AMONG ADOLESCENT AND YOUNG ADULT STUDENTS OF NAVODAYA GROUP OF INSTITUTIONS - PALLAVI, KOLAN; K., HARSHITHA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Polycystic ovary syndrome (PCOS) is considered to be the most common endocrine disorder in women of reproductive age. The objective of this study was to calculate the prevalence of PCOS in Navodaya group of institutions based on Rotterdam criteria. Methods: A prospective study of 500 girls of Navodaya group of institutions (school, medical, dental, and nursing, pharmacy, physiotherapy and engineering students) aged 13 to 25 y who underwent clinical examination. Out of which, 68 girls with oligomenorrhea and/or hirsutism were invited for biochemical, hormonal, and ultrasonographic evaluation for diagnosis of PCOS by Rotterdam criteria. Results: Out of 500 girl students, 68 girls satisfied Rotterdam’s criteria for PCOS. Under the Rotterdam criteria, the estimated prevalence of PCOS in adolescent and young adult students was 13.6%. Conclusion: Prevalence of PCOS in adolescent and young adult students of Navodaya Group of Institutions was 13.6%. This draws attention to the issue of early diagnosis in adolescent girls.